Reliability, validity, and sensitivity of a specific agility test and its relationship with physical fitness in karate athletes - Hassan, S. B.; Negra, Y.; Uthoff, A.; Chtara, M.; Jarraya, M. (Frontiers in Physiology, 2022)
The aim of this study was to investigate the validity and reliability of a developed specific karate agility test (SKAT) and to examine its relationship with physical fitness. A total of 36 karateka voluntarily participated in this study. During two separate sessions, international and national ranked athletes completed the SKAT by performing three changes of direction (CoD): two in a preplanned manner and one in response to a stimulus that was provided by a live tester (Light tester). Assessment of CoD, horizontal jumping ability, 5 and 10 m sprint time, and dynamic balance were also applied during these two occasions. To evaluate SKAT`s construct validity, two groups were recruited based on their karate results: High- vs. low-ranked athletes. Reliability, validity, and sensitivity of the SKAT were examined from the intraclass correlation coefficient (ICC), standard error of measurement (SEM), smallest worthwhile change (SWC), and receiving operator characteristic analysis. Regarding relative and absolute reliability, the ICC of SKAT was excellent at >0.95 and the SEM was <5%. According to the sensitivity analysis, the power to detect small performance changes can be rated as "good" in karate athletes (SWC > SEM). The SKAT showed a moderate relationship with the CoD, jumping, sprint, and dynamic balance tests. High-ranked athletes were better than their low-ranked counterparts on SKAT (Cohen`s d = 2.00). The area under the receiving operator characteristic curve was 0.76. To sum up, the SKAT is a reliable and valid tool to assess the agility performance of karatekas and can be used by conditioning trainers to detect "true" performance changes.